Design of structural elements : concrete, steelwork, masonry and timber designs to British standards and Eurocodes - Arya, Chanakya (Spon Press, 2009)
This concise introduction to the design of structural elements in concrete, steel, timber, masonry and composites provides up-to-date design principles and guidance in line with both British Standards and Eurocodes.